Improvements in the quality of the parent-child relationship following treatment with an integrated family approach - Stolper, Hanna; Imandt, Lieke; van Doesum, Karin; Steketee, Majone (Frontiers in Psychiatry, 2024)
Objective: This study investigated changes in the emotional availability of the parent and the child in their dyadic relationship, parental reflective functioning, and parental perception of their relationship with their child after an integrated family approach to treatment in adult and child mental health care services. The aim of the study is to investigate if an integrated family approach in treatment contributes to good practice in mental health care.Background: Children of parents with a mental disorder are at increased risk for developing mental health problems themselves during lifetime. Infants are extremely vulnerable for environmental influences. Parents with mental disorders are at risk for mis-attuned behavior and non-optimal emotional availability. This increases the risk of adverse cascading effects on the parent-child relationship and child development. A secure parent-child relationship is an important protective factor against the intergenerational transmission of mental disorders.Although treatment of the parental mental disorder is important, it does not automatically change undesirable patterns in the parent-infant relationship. Therefore, an integrated family approach to mental health treatment is recommended.Methods: This study involved a mixed methods design using questionnaires, an observation instrument and semi-structured interviews. The variables examined were the quality of the parent-child interaction, the parental perspective on their relationship with the child, their problems with child upbringing, and on their parental reflective functioning. The clinical sample consisted of 50 patients with a variety of mental disorders and their young children.After finishing the integrated treatment the quality of the parent-child interaction had improved significantly. Likewise, we found a significant improvement in parental perception regarding the relationship with the child and the parental role. The majority of the parents interviewed showed that they were able to mentalize about themselves, their child and their relationship with the child, but the data from the questionnaire showed mixed results regarding parents' reflective functioning.Treatment with an integrated family approach to mental health care in which the parental role of the patient, the young child, and the parent-infant relationship are integrated in treatment, can be a valuable addition to the current practice of mental health care in which patients are commonly perceived as an individual.